(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
This paper explores the growing trend of body enhancement surgeries in Nigeria, focusing on its evolution, motivations, challenges, and the government’s responses and shortcomings. By examining the changing dynamics of body enhancement practices, the paper aims to contribute to the broader conversation surrounding body image, identity, and the societal pressures influencing individuals’ choices about their physical appearance. Using a qualitative methodology, the study gathered data from both primary and secondary sources. Primary data was collected through oral interviews and observations, while secondary data was collected from books, newspapers, and journals. The findings reveal that both men and women undergo body enhancement surgeries, although it is more prevalent among women. It further found that body modification is an age-old practice which has taken on new dimensions in recent years due to factors like body shaming, peer pressure, media influences, global beauty trends, and the desire for the "perfect" body. This has led to a rise in botched surgeries and even fatalities, especially when performed by non-professionals or quacks. The government’s response to these issues has been relatively passive, allowing the problem to grow and enabling the entry of unqualified practitioners. The study also highlights a debate between modernity and tradition, with proponents of modernity seeing body enhancement as a contemporary trend while traditionalists advocate for embracing one’s natural body. The findings emphasise the importance of fostering critical discussions on the consequences of body enhancement surgeries, promoting healthy selfimage, and accepting diverse body types in Nigerian society.